Comprehensive Immune Profiling of a Kidney Transplant Recipient With Peri-Operative SARS-CoV-2 Infection: A Case Report - Sherwood, Karen R.; Nicholl, David D. M.; Fenninger, Franz; Wu, Vivian; Wong, Paaksum; Benedicto, Vince; Cina, Davide P.; Wang, Meng; Pobran, Taylor D.; De Marco, Mari L.; Márquez, Anna Citlali; Jassem, Agatha N.; et al. (Frontiers in Immunology, 2021)
To date there is limited data on the immune profile and outcomes of solid organ transplant recipients who encounter COVID-19 infection early post-transplant. Here we present a unique case where the kidney recipient’s transplant surgery coincided with a positive SARS-CoV-2 test and the patient subsequently developed symptomatic COVID-19 perioperatively. We performed comprehensive immunological monitoring of cellular, proteomic and serological changes during the first 4 critical months post-infection. We showed that continuation of basiliximab induction and maintenance of triple immunosuppression did not significantly impair the host’s ability to mount a robust immune response against symptomatic COVID-19 infection diagnosed within the first week post-transplant.